Financial management - Krishna Reddy, B.; Appannaiah, H. R.; Satyaprasad, B. G. (Jaipur, India : Printwell, 1999)
Study confined to the financial management of the spinning mills in private sector in Andhra Pradesh, 1977-86.
Includes bibliographical references (p. [269]-285).
Keywords: Cotton textile industry -- India -- Andhra Pradesh -- Finance